Technological knowledge application on academic writing English education study program students - Irfan Irfan; Sofendi Sofendi; Machdalena Vianty (English Review: Journal of English Education, 2020)
Technological knowledge plays a role in academic writing such as assisting in finding suitable references, checking plagiarism, and publishing the article. However, technological knowledge does not always provide benefits in academic writing. Technological knowledge may affect the writers’ mentality to take shortcut in finishing and checking their writing. The objectives of this study were: (1) to find out the technological knowledge level of English education study program students, (2) to find out how English education study program students applied their technological knowledge in academic writing, and (3) to find out the problems English education study program students encountered in applying their technological knowledge in academic writing. The study’s participant was 13 students from class B 2016 Palembang of English Education Undergraduate Program along with the latest lecturer that teaches them writing. This research used descriptive qualitative design. The data were collected by questionnaire, observation, interview, and document gathering. Percentage calculation, transcribing, and triangulation were used to analyze data. The findings showed that (1) The technological knowledge level of the participants is level two Technical Maxim, (2) the participants applied technological knowledge on academic particularly in finding references and structuring idea, and (3) the participants have several problems in applying technological knowledge in academic writing, such as in citing references correctly, avoiding tendency to copy-and-paste, structural error due to using automatic correction, and paper formatting.